Tremor in inflammatory neuropathies. Issue 11 (5th September 2012) - Saifee, Tabish Aziz; Schwingenschuh, Petra; Reilly, Mary M; Lunn, Michael P T; Katschnig, Petra; Kassavetis, Panagiotis; Pareés, Isabel; Manji, Hadi; Bhatia, Kailash; Rothwell, John C; Edwards, Mark J
Abstract : Background: Tremor is known to occur in patients with neuropathies although its reported prevalence varies widely. Tremor has been shown to cause disability in children with Charcot–Marie–Tooth disease but no data exit about the disability caused by tremor in inflammatory neuropathies. Little is known about the response of neuropathic tremor to treatment and why it selectively occurs in some people and not others. Methods: This case control study investigates the presence and severity of tremor in 43 consecutively recruited patients with inflammatory neuropathies at the National Hospital for Neurology and Neurosurgery, London. Clinical assessment, including Fahn–Tolosa–Marin Scale for tremor, sensory scores, power scores and Overall Neuropathy Limitations Scale, were recorded. Results of nerve conduction studies were retrieved and assessed. Nine patients' tremors were recorded with accelerometry. Results: Tremor was most common in IgM paraproteinaemic neuropathies, as previously reported, but also occurred in 58% of those with chronic inflammatory demyelinating polyradiculoneuropathy and 56% of those with multifocal motor neuropathy with conduction block. We describe, for the first time, tremor in the majority of patients with multifocal motor neuropathy with conduction block. Tremor in all of these patients seems generally refractory to treatment except in a small number of cases where tremor improves with treatment of the underlying neuropathy. We provide evidence that tremor may add to disability in patients with inflammatory neuropathy. Mean tremor frequency was 6 Hz and did not vary with weight loading. We demonstrate for the first time that although tremor severity correlates with F wave latency, it is not sufficient to distinguish those with, from those without, tremor. Conclusion: Tremor in inflammatory neuropathies is common, adds to disability and yet does not often respond to treatment of the underlying neuropathy. When present, tremor severity is associated with F wave latency.